Digestibility of sorghum rations with different tannin levels content and their effect on pig metabolism (Semiárida, 2020)
Four diets for growing pigs based on grain sorghums with different tannin levels were approved: High (T3), medium (T2), low (T1), and a very low one as a control (T0). Diets were isonitrogenous (16%GP) and isoenergetic (13,8 MJ/kg) ones; they were valued in four replicate animals received each diet using a randomized design, with one pig DxHxLW, in metabolism cages. No significative differences were found (p> 0,05) for daily gain and daily feed intake on treatments, observing an unfavorable slight biological difference on T3 on feed gain (control: 2.7:1 vs. T1: 2,8:1, T2: 2,8:1 and T3: 3,0:1). The largest energy loss was on the feces and relatively slight on urine. The energetic maintenance cost significatively favorable (p
Keywords: tannin; digestibility; pig metabolism